ChemInform Abstract: Nucleophilic Addition Reactions of Nitriles to Nitrones under Mild Silylation Conditions. Issue 7 (29th January 2015) - Yoshimura, Fumihiko; Abe, Taiki; Tanino, Keiji
Abstract The synthetic versatility of the addition products is further examined by the transformation of the cyano group in (XIa) into a carboxamide, a carboxylic acid or an aminomethyl functionality.